Phosphoproteomics reveals that cinobufotalin promotes intrahepatic cholangiocarcinoma cell apoptosis by activating the ATM/CHK2/p53 signaling pathway - Xia, Zhili; Li, Minzhen; Hu, Meng; Lin, Yanyan; Atteh, Lawrence Lawer; Fu, Wenkang; Gao, Long; Bai, Mingzhen; Huang, Chongfei; Yue, Ping; Liu, Yu; Meng, Wenbo (Frontiers in Oncology, 2022)
Intrahepatic cholangiocarcinoma (ICC) is a malignant tumor that originates from bile duct’s epithelial cells and is usually characterized by insidious symptoms and poor prognosis. Cinobufotalin (CB), an active ingredient obtained from the Traditional Chinese Medicine ChanSu, is purported to exhibit a wide range of antitumorigenic activities. However, the mechanism by which it achieves such pharmacological effects remains elusive. Here, we disclosed the mechanism of action by which CB inhibits ICC cells. Initial experiments revealed that the proliferation of RBE and HCCC-9810 cells was significantly inhibited by CB with IC50 values of 0.342 μM and 0.421 μM respectively. CB induced the expression of caspase-3 subsequently leading to the apoptosis of ICC cells. Phosphoproteomics revealed that the phosphorylation of many proteins associated with DNA damage response increased. Kinase-substrate enrichment analysis revealed that ATM was activated after CB treatment, while CDK1 was inactivated. Activated ATM increased p-CHK2-T68 and p-p53-S15, which promoted the expression of FAS, DR4 and DR5 and triggered cell apoptosis. In summary, this work reveals the role of CB in inducing DNA damage and cell apoptosis involved in the activation of the ATM/CHK2/p53 signaling pathway, and indicates that CB may serve as a chemotherapeutic drug candidate for ICC treatment.